The generals of Saratoga : John Burgoyne & Horatio Gates - Mintz, Max M., 1919- (Yale University Press, 1990)
This lively and colorful work offers a fresh account of the Saratoga campaign of 1777 through the lives of its opposing generals -- John Burgoyne, the British commander, and Horatio Gates, the American (but British-born) commander. The book vividly portrays the two men and the events that developed around them. It is the fullest discussion ever written about both the American and British dimensions of this campaign, the only engagement in the Revolutionary War in which an all-American army captured a major British force. Max M. Mintz has combed the letters and diaries of survivors to craft on-the-scene descriptions of the British taking of Ticonderoga, the slaughter at Hubbardton, the victory of American militia at Bennington, the two hard-fought battles of Saratoga, and the surrender of Burgoyne. Throughout the book new insights are revealed: Burgoyne's difficulties with his superiors, the deep roots of Gates's quarrels with George Washington and Benedict Arnold, the factors that caused Burgoyne to choose the land rather than the water route from Lake Champlain to the Hudson River, and the broken promise that misled Burgoyne to believe that Sir Henry Clinton would come to save him. - Jacket flap.